Análise do impacto das plataformas pay-as-you-go de computação em nuvem na construção e precificação de software - Barbosa, Fernando Pires (2011)
Cloud computing is a new paradigm that is changing the way we consume IT resources. One of the major changes is related to the pay-as-you-go pricing model. There are several kinds of cloud services being offered and the best option for software developers are Platform as a Service (PaaS). Even with cloud computing beeing a buzzword nowadays, there are few studies being developed to cover the way it will impact the software development. This thesis intents to contribute to fill this gap and provide the basis for new detailed studies about this subject. It presents an analysis about the main aspects in software delevopment that must be afected by the pay-as-you-go cloud model and highlights some of theses changes trough a case study. We noticed significant changes in the following areas: software pricing, performance benchmarks, software development estimation and requirements engineering. These changes are related to a new paradigm in which the IT resources used by software systems will directly impact the software price at all. This should also generate changes in how we deal with software optimization improvement. There is a large research field to be explored and this thesis contributes to point ou some directions.